Digital Promotion Training on Making Animated Stickers for Students and Teachers of the Visual Communication Design Department at SMKN 1 Surabaya - Suminto, Miftahul Adi; Setiyoko, Nanang; Dewanto, Thomas Hanandry; Afandi, Haekal Ridho; Pratama, Yudha Herlambang Cahya; Hermansyah, Deny; Suryani, Tatik (Institut Teknologi Nasional, Bandung, 2024)
In the digital era, promotional skills through visual media are becoming increasingly important, especially for students and teachers in the field of Visual Communication Design (DKV). This community service activity aims to improve the digital promotion competence of students and teachers majoring in DKV at SMKN 1 Surabaya through training in making animated stickers. The method used in this research is qualitative descriptive research, with the participation of 17 students and 9 DKV teachers. This training involves several stages, starting from an introduction to the basics of making animated stickers, manufacturing practices, to implementation in digital promotional strategies. The research results show that this training was successful in improving students' and teachers' skills in creating effective animated stickers for digital promotions. Apart from that, training participants also showed an increased understanding of the importance of using animated stickers in more creative and attractive promotional campaigns. Thus, this training can be used as a model for developing other digital promotion skills in vocational education institutions.